2021
DOI: 10.3390/metabo11080546
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Metabolomic Biomarkers for the Intake of Sugar-Sweetened and Low-Calorie Sweetened Beverages

Abstract: Intake of added sugars (AS) is challenging to assess compared with total dietary sugar because of the lack of reliable assessment methods. The reliance on self-reported dietary data in observational studies is often cited as biased, with evidence of AS intake in relation to health outcomes rated as low to moderate quality. Sugar-sweetened beverages (SSBs) are a major source of AS. A regular and high intake of SSBs is associated with an overall poor diet, weight gain, and cardiometabolic risks. An elevated inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…This is unexplained at this time because these metabolites tend to be associated with dietary animal protein [8,9]. Previous studies reported that plasma L-alanine, carbon-13, D-glucose and 2-piperidinone are potential plasma biomarkers of sugar sweetened beverage intake [19,20]. Similar findings in terms of the SC diet were not observed in the current study.…”
Section: Discussionsupporting
confidence: 74%
“…This is unexplained at this time because these metabolites tend to be associated with dietary animal protein [8,9]. Previous studies reported that plasma L-alanine, carbon-13, D-glucose and 2-piperidinone are potential plasma biomarkers of sugar sweetened beverage intake [19,20]. Similar findings in terms of the SC diet were not observed in the current study.…”
Section: Discussionsupporting
confidence: 74%
“…By contrast, most diet studies rely on food frequency questionnaires that do not query brand name information and therefore do not capture ArtSw content apart from diet beverages. To date, no objective biomarkers of habitual ArtSw intake have been validated for ArtSw intake [ 31 , 32 ], so our approach of averaging ArtSw intake at multiple time points remains one of the more robust methods for assessing ArtSw intake. For AT outcomes, ATs and muscle composition were quantified using CT imaging, which precisely evaluates specific body AT compartment volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limitations described above, the CIR Ala , alone or in combination with other CIR AA s, shows promise as a biomarker for AS or SSB intake in certain populations and warrants further study [ 34 ]. The only other proposed biomarker for AS intake is whole-tissue CIRs, which have been shown to correlate more with meat or animal protein intakes in various studies across populations [ 20 , 22 , 29 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prediction model for AS intake developed from blood CIR demonstrated poor performance in external validation; specifically, high intakes were underestimated [ 39 ]. There has been some metabolomic exploration of SSB intake biomarkers [ 40 ], but this approach has the limitation of identifying compounds that may not be present in all SSBs (low sensitivity) or may be present in other foods (low specificity) [ 34 ]. Metabolomic biomarkers are also often limited to indicating short-term intake, whereas plasma and RBC CIR AA s integrate diet over several weeks or months [ 18 ].…”
Section: Discussionmentioning
confidence: 99%